The Evaluation of Judicial Report Process of 1306 Patients with Nasal Fracture - Karbeyaz, Kenan; Düzer, Selma; Düzer, Sertaç; Balcı, Yasemin (The Bulletin of Legal Medicine, 2015)
Objective: Nasal fracture is frequently seen in facial region traumas due to its anatomical properties and location. Some problems are encountered during report process of nasal fracture patients in Judicial Medicine Director Office. In this study, we have aimed to emphasize the evaluation of nasal fractures for judicial traumatology and the any problem during judicial reportprocess. Materials and methods: Between 01 June 2011 and 31 May 2014, 24306 judicial report which ordered by Eskişehir Judicial Medicine Director Office were investigated and then, 1306 patients with nasal fracture were evaluated retrospectively and included to the study. Results: Totally 2104 correspondences were performed for report preparation according to trauma’s degree in 1306 patients. Additional document, graphy and consultation were requested once in 764 patients and twice in 17 patients. The ages and sex of the patients were found similar with the literature. Conclusion: We concluded that the employment of Judicial Medicine Specialists should be increased in health institutions in long term and judicial medicine director offices should be integrated to the databases of health institutions in cities in short-term. Keywords: Nasal fracture. Judicial report. Trauma.